The Routledge history of global war and society
1 online resource
Keywords: "The Routledge History of Global War and Society offers a sweeping introduction to the most significant research on the causes, experiences, and impacts of war throughout history. This collection of twenty-seven essays by leading historians demonstrates how war and society studies have dramatically expanded the chronological, geographic, and thematic breadth of the field of military history. Each chapter addresses the ways in which recent scholarship has integrated cultural, ethical, environmental, medical, and ideological factors to explain both conventional conflicts and genocide, terrorism, and other forms of mass violence. The broad scope of the collection make it the perfect primer for scholars and students seeking to understand the complex interactions of warfare and those affecting and affected by conflict."--Provided by publisher.